Accurate Determination of Adsorption-Energy Differences of Metalloporphyrins on Rutile TiO2(110) 1 x 1 - Muth, Maximilian; Wolfram, Alexander; Kataev, Elmar; Köbl, Julia; Steinrück, Hans-Peter; Lytken, Ole (Langmuir, 2022)
Understanding the adsorption of organic molecules on surfaces is of essential importance for many applications. Adsorption energies are typically measured using temperature-programmed desorption. However, for large organic molecules, often only desorption of the multilayers is possible, while the bottom monolayer in direct contact to the surface cannot be desorbed without decomposition. Nevertheless, the adsorption energies of these directly adsorbed molecules are the ones of the most interest. We use a layer-exchange process investigated with X-ray photoelectron spectroscopy to compare the relative adsorption energies of several metalated tetraphenylporphyrins on rutile TiO2(110) 1 x 1. We deposit a mixture of two different molecules, one on top of the other, and slowly anneal above their multilayer desorption temperature. During the slow heating, the molecules begin to diffuse between the layers and the molecules with the stronger interaction with the surface displace the weaker-interacting molecules from the surface and push them into the multilayer. The multilayers eventually desorb, leaving behind a monolayer of strongly interacting molecules. From the ratio of the two different porphyrin molecules in the residual monolayer and the desorbed multilayer, we can calculate the equilibrium constant of the layer-exchange process and thereby the difference in adsorption energy between the two different porphyrin molecules.
CRIS-Team WoS Importer:2022-07-29

Adsorption of phenylphosphonic acid on rutile TiO2(110) - Köbl, Julia; Wechsler, Daniel; Kataev, Elmar; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (Surface Science, 2020)
Binding of functionalized organic molecules to oxide surfaces is an important step in the rational design of molecular devices. In the present investigation, we used synchrotron radiation photoelectron spectroscopy and near-edge X-ray absorption fine structure spectroscopy to determine the binding mode, electronic structure and adsorption geometry of phenylphosphonic acid (PPA) on TiO2(110)–(1 × 1). We found that PPA multilayers desorb below 380 K leaving a compact PPA monolayer adsorbed on the surface, which remains stable up to 780 K. In the 380–520 K temperature range, molecules are anchored to the surface via a single P–O–Ti covalent bond (monodentate configuration). Furthermore, the phenyl ring is tilted 45° with respect to the surface plane and it either forms 45° or is randomly oriented with respect to [001] crystallographic direction. Raising the temperature above 520 K partially transforms the monodentate configuration to a mixed one- and twofold deprotonated bidentate binding mode, presumably after surface hydroxyl groups leave the surface as water molecules. This change in molecular binding does not alter the molecular electronic structure nor the adsorption geometry, which remain essentially unchanged.
CRIS-Team Scopus Importer:2020-06-05

Benzohydroxamic acid on rutile TiO2(110)-(1×1)– a comparison of ultrahigh-vacuum evaporation with deposition from solution - Köbl, Julia; Fernández, Cynthia C.; Augustin, Lisa-Marie; Kataev, Elmar; Franchi, Stefano; Tsud, Nataliya; Pistonesi, Carolina; Pronsato, M. Estela; Jux, Norbert; Lytken, Ole; Williams, Federico J.; Steinrück, Hans-Peter (Surface Science, 2022)
Hydroxamic acids are an interesting anchor group for organic molecules on oxide surfaces, but very few studies exist on their adsorption on well-defined single-crystal surfaces under well-defined conditions. In the present paper, we use X-ray photoelectron spectroscopy to follow the adsorption of benzohydroxamic acid on a rutile TiO2(110)-(1×1) single-crystal surface. We compare evaporation in ultrahigh vacuum with deposition from ethanol and acetonitrile solutions. Furthermore, we carried out density functional theory calculations to support the assignment of adsorbates. Several species appear on the surface, which are most evident in the N 1s region. The low-coverage species can be explained as originating from a hydroxamate, and decomposed species related to oxygen vacancies or defects. Identification of the high-coverage species, however, remains elusive, and several possibilities are discussed.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Benzohydroxamic acid; Density functional theory calculations; TiO; X-ray photoelectron spectroscopy (XPS)

Controlling the Self-Metalation Rate of Tetraphenylporphyrins on Cu(111) via Cyano Functionalization - Lepper, Michael; Köbl, Julia; Zhang, Liang; Meusel, Manuel; Hölzel, Helen; Lungerich, Dominik; Jux, Norbert; De Siervo, Abner; Meyer, Bernd; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2018)
The reaction rate of the self-metalation of free-base tetraphenylporphyrins (TPPs) on Cu(111) increases with the number of cyano groups (n=0, 1, 2, 4) attached at the para positions of the phenyl rings. The findings are based on isothermal scanning tunneling microscopy (STM) measurements. At room temperature, all investigated free-base TPP derivatives adsorb as individual molecules and are aligned with respect to densely packed Cu substrate rows. Annealing at 400K leads to the formation of linear dimers and/or multimers via CN-Cu-CN bonds, accompanied by self-metalation of the free-base porphyrins following a first-order rate equation. When comparing the non-cyano-functionalized and the tetracyano-functionalized molecules, we find a decrease of the reaction rate by a factor of more than 20, corresponding to an increase of the activation energy from 1.48 to 1.59eV. Density functional theory (DFT) calculations give insights into the influence of the peripheral electron-withdrawing cyano groups and explain the experimentally observed effects.
Keywords: cyano functionalization; porphyrinoids; scanning tunneling microscopy; self-metalation; surface chemistry

CORRIGENDUM: Adsorption of phenylphosphonic acid on rutile TiO2(110) (Surface Science (2020) 698, (S0039602819309410), (10.1016/j.susc.2020.121612)) - Köbl, Julia; Wechsler, Daniel; Kataev, Elmar; Williams, Federico J.; Tsud, Nataliya; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (Surface Science, 2022)
In the original version of this article, Fig. 6 was plotted incorrectly, since in the input file the data on the polar angle axis were inserted in the inverse order. The correct Fig. 6 is shown below (caption remains unchanged). The error also concerns the deduced angles of the molecular plane relative to the surface plane (polar tilt angle), which are addressed in the manuscript on page 5, left column. The text should correctly read: "Fitting yields a polar tilt angle of 25° of the phenyl ring plane with respect to the surface normal with an azimuthal angle of 42° for the monodentate monolayer (380 K), and a polar tilt angle of 26° with an azimuthal angle of 43° for the mixed bidentate (or mono- and tridentate) monolayer (650–780 K). The fitting procedure was performed following the procedure from Ref. [37] In line with the unchanged electronic structure, the molecular orientation does not change (within the margin of error) when a monodentate monolayer of phenylphosphonic acid is annealed to form a mixed bidentate layer. Notably, for the onefold deprotonated bidentate, a polar tilt angle of ∼40° is estimated from Fig. 8 in Ref. [9]. For comparison, we note that 0.85 ML of phenylphosphonic acid adsorbs on anatase TiO2(101) surfaces at room temperature with a phenyl ring tilted 25° with respect to the surface normal.” Furthermore, the denoted value for the polar angle in the abstract and the summary should be changed to 25° The corrected texts read: Abstract: “Furthermore, the phenyl ring is tilted ∼25º with respect to the surface normal and it either forms 45° or is randomly oriented with respect to [001] crystallographic direction.” Conclusion: “Both monolayers possess essentially the same electronic structure with molecules tilted ∼25° with respect to the surface normal and with either a random azimuthal orientation or a 45° one.”
CRIS-Team Scopus Importer:2021-12-24

Hungry Porphyrins: Protonation and Self-Metalation of Tetraphenylporphyrin on TiO2(110)-1 x 1 - Köbl, Julia; Wang, Tao; Wang, Cici; Drost, Martin; TU, Fan; Xu, Qian; Ju, Huanxin; Wechsler, Daniel; Franke, Matthias; Pan, Haibin; Marbach, Hubertus; Steinrück, Hans-Peter; et al. (ChemistrySelect, 2016)
We have studied the adsorption and self-metalation of tetraphenylporphyrin (2HTPP) on TiO2(110) -1 x 1 with X-ray Photoelectron Spectroscopy (XPS) and Scanning Tunneling Microscopy (STM). Upon adsorption at room temperature the first monolayer of 2HTPP is protonated by protons from the surface, forming porphyrin diacid (4HTPP(2+)). In STM, single molecules with low mobility and no long-range order were observed. As the surface is heated to 400 K, any unprotonated 2HTPP molecules in the second layer metalate, forming titanyl tetraphenylporphyrin (TiOTPP), but the protonated molecules in the first layer remain. As the surface is heated further to 550 K even the protonated 4HTPP(2+) molecules metalate and only TiOTPP remain on the surface.
Keywords: Adsorption; Porphyrinoids; Oxide Surfaces; Surface Chemistry; Titania

"Inverted'' porphyrins: a distorted adsorption geometry of free-base porphyrins on Cu(111) - Lepper, Michael; Köbl, Julia; Schmitt, Tobias; Gurrath, Martin; De Siervo, Abner; Schneider, M. Alexander; Steinrück, Hans-Peter; Meyer, Bernd; Marbach, Hubertus; Hieringer, Wolfgang (Chemical Communications, 2017)
Based on density functional theory calculations combined with experimental results, we report and discuss an extremely distorted, "inverted'' adsorption geometry of free-base tetraphenylporphyrin on Cu(111). The current findings yield new insights into a wellstudied system, shedding light on the peculiar molecule-substrate interaction and the resulting intramolecular conformation.

Phenylphosphonic Acid on Rutile TiO2(110): Using Theoretically Predicted O 1s Spectra to Identify the Adsorption Binding Modes - Wolfram, Alexander; Muth, Maximilian; Köbl, Julia; Mölkner, Andreas; Mehl, Sascha; Tsud, Nataliya; Steinrück, Hans-Peter; Meyer, Bernd; Lytken, Ole (Journal of Physical Chemistry C, 2024)
We have studied the adsorption of phenylphosphonic acid on rutile TiO2(110)-(1 × 1) using high-resolution synchrotron-radiation photoelectron spectroscopy and near-edge X-ray absorption fine-structure spectroscopy (NEXAFS). Upon adsorption at room temperature, we observe a complex O 1s spectrum, a single P 2p multiplet and the disappearance of small polarons in the Ti 2p and valence-band regions. Upon heating to 450-500 K, the O 1s spectrum changes, an additional P 2p species appears, the polaron signals reappear even stronger and NEXAFS indicates a more flat-lying molecule. Using density functional theory (DFT), we have determined the most stable adsorption configurations on the surface. For these configurations, we have calculated the O 1s and P 2p binding-energy positions of all oxygen and phosphorus atoms, including the first three trilayers of the TiO2(110) substrate. In addition, we have used the orientations of the phenyl rings from the DFT structures to calculate the expected polar and azimuthal angular dependencies in carbon K-edge NEXAFS. This allows us to compare our calculated adsorption configurations with the experimental observations. Below 450 K, we find a singly deprotonated bidentate species to be in perfect agreement with the experimental data. Above 500 K, the desorption of water creates oxygen vacancies, and we find a mixed bidentate and rotated-tridentate adsorption structure to be in good agreement with the experimental observations.
CRIS-Team Scopus Importer:2024-07-26

Probing the Roughness of Porphyrin Thin Films with X-ray Photoelectron Spectroscopy - Kataev, Elmar; Wechsler, Daniel; Williams, Federico J.; Köbl, Julia; Tsud, Natalia; Franchi, Stefano; Steinrück, Hans-Peter; Lytken, Ole (ChemPhysChem, 2020)
Thin-film growth of molecular systems is of interest for many applications, such as for instance organic electronics. In this study, we demonstrate how X-ray photoelectron spectroscopy (XPS) can be used to study the growth behavior of such molecular systems. In XPS, coverages are often calculated assuming a uniform thickness across a surface. This results in an error for rough films, and the magnitude of this error depends on the kinetic energy of the photoelectrons analyzed. We have used this kinetic-energy dependency to estimate the roughnesses of thin porphyrin films grown on rutile TiO2(110). We used two different molecules: cobalt (II) monocarboxyphenyl-10,15,20-triphenylporphyrin (CoMCTPP), with carboxylic-acid anchor groups, and cobalt (II) tetraphenylporphyrin (CoTPP), without anchor groups. We find CoMCTPP to grow as rough films at room temperature across the studied coverage range, whereas for CoTPP the first two layers remain smooth and even; depositing additional CoTPP results in rough films. Although, XPS is not a common technique for measuring roughness, it is fast and provides information of both roughness and thickness in one measurement.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Growth; Porphyrin molecules; Thin films; X-ray photoelectron spectroscopy

Wet-chemically prepared porphyrin layers on rutile tio2(110) - Wechsler, Daniel; Carolina Fernandez, Cynthia; Köbl, Julia; Augustin, Lisa-Marie; Stumm, Corinna; Jux, Norbert; Steinrück, Hans-Peter; Williams, Federico Jose; Lytken, Ole (Molecules, 2021)
Porphyrins are large organic molecules that are interesting for different applications, such as photovoltaic cells, gas sensors, or in catalysis. For many of these applications, the interactions between adsorbed molecules and surfaces play a crucial role. Studies of porphyrins on surfaces typically fall into one of two groups: (1) evaporation onto well-defined single-crystal surfaces under well-controlled ultrahigh vacuum conditions or (2) more application-oriented wet chemical deposition onto less well-defined high surface area surfaces under ambient conditions. In this study, we will investigate the wet chemical deposition of 5-(monocarboxyphenyl)-10,15,20-triphenylporphyrin (MCTPP) on well-defined rutile TiO2 (110) single crystals under ambient conditions. Prior to deposition, the TiO2(110) crystals were also cleaned wet-chemically under ambient conditions, meaning none of the preparation steps were done in ultrahigh vacuum. However, after each preparation step, the surfaces were characterized in ultrahigh vacuum with X-ray photoelectron spectroscopy (XPS) and the result was compared with porphyrin layers prepared in ultrahigh vacuum (UHV) by evaporation. The differences of both preparations when exposed to zinc ion solutions will also be discussed.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Interfaces; Metalation; Oxide surfaces; Porphyrins; Wet chemical preparation